Peningkatan Pemahaman Penyakit Thalasemia pada Anggota PMR Tingkat Wira di SMA Terpadu Ar-Risalah Cijantung IV Kabupaten Ciamis: Increased Understanding of Thalassemia Disease in PMR Members at the Wira Level at Ar-Risalah Integrated High School Cijantung IV Ciamis Regency - Setiawan, Doni; Firdaus, Nabil Ridla; Ariyadi, Rivana; Indriastuti, Marlina (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
In the last five years, there has been an increase in thalassemia beta major patients in the Ciamis Regency. Thalassemia education and counseling for students is needed because the thalassemia prevention program movement must be carried out to support the emergence of new thalassemia major cases. Palang Merah Remaja (PMR) of Ar-Risalah Ciamis Integrated High School is one of the forums to foster students in developing an attitude of martyrdom. The purpose of this service activity is to train and empower PMR students of Ar-Risalah Ciamis Integrated High School as thalassemia cadres. The method used is the lecture method with ebook media. Participants in this activity were 12 members of the PMR Wira SMA Teradu Ar-Risalah which was held in the classroom of SMA Terpadu Ar-Risalah on September 7, 2023. The instrument used is a questionnaire distributed via Google form during the pre-test and post-test which will then determine the level of knowledge of the participants which will be narrated as an indicator of the success of the activity. The results of this service activity showed an increase in the average value of the participants' post-test of 83%. Educational activities using ebooks can increase participants' understanding of thalassemia.